2019
DOI: 10.1139/tcsme-2018-0221
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of high-speed turning parameters for Inconel 713C based on Taguchi grey relational analysis

Abstract: In this work, a propelled dynamic approach, Taguchi grey relational analysis has been employed to estimate the impact of untreated and cryogenically treated and oil-quenched WC-Co tools in high-speed turning of Inconel 713C alloy on cutting force and surface roughness. Taguchi grey relational analysis is executed to maximize the high-speed turning of Inconel 713C alloy taking into account various operating parameters (cutting speed, feed rate, and depth of cut). The L27 orthogonal array has been utilized to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…6 with cutting speed (v) of 60 m/min, feed rate (f) of 0.3 mm/rev and depth-of-cut (d) of 0.25 mm were the attained optimal input machining parameters. Similar approach was used by Parthiban et al [11], Vasudevan et al [24], Pedkarand and Karidkar [25], Pawade and Joshi [26] and obtained results with their study were found to be in good agreement with experimental results attained in this study.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…6 with cutting speed (v) of 60 m/min, feed rate (f) of 0.3 mm/rev and depth-of-cut (d) of 0.25 mm were the attained optimal input machining parameters. Similar approach was used by Parthiban et al [11], Vasudevan et al [24], Pedkarand and Karidkar [25], Pawade and Joshi [26] and obtained results with their study were found to be in good agreement with experimental results attained in this study.…”
Section: Resultssupporting
confidence: 90%
“…The optimal process parameters were achieved (60 m/min for speed, 0.05 mm/rev for feed and 0.2 mm for depth of cut) from the selected range of L9 orthogonal array. Parthiban et al [11] employed Taguchi grey relational analysis for estimating the impact of turning Inconel 713C alloy with different tools (WC-Co tool and cryogenically treated and oil-quenched WC-Co tools). The analysis was performed with L27 orthogonal array with operating parameters (cutting speed, feed rate, and depth of cut) for recognizing the components influencing surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…This is in good agreement with recent researches conducted by Zhuang et al [20] and Suresh Kumar et al [22]. In addition, this hybrid technique for optimization (Taguchi-Grey) considerably improves the optimization of the output process responses; this also is in good agreement with the findings of Kumar and Dhanabalan [38], and Parthiban et al [39].…”
Section: Accuracy and Prediction Errors Comparisonsupporting
confidence: 92%
“…The experimental approach, as the basis of scientific research, is increasingly supplemented with modeling and optimization methods. Response surface methodology [21], artificial neural network [22], fuzzy method [23], gray relational analysis [24], particle swarm optimization [25] and genetic algorithm [26] are widely used to reduce the cost and time of experimental research.…”
Section: Introductionmentioning
confidence: 99%